Optimal Design of Social Insurance Frameworks in National Health Insurance - Murty, Theta; Sukarmi; Widyanti, Yenny Eta; Dewi, Amelia Sri Kusuma (Universitas Muhammadiyah Malang, 2024)
The national health insurance program in Indonesia aims to ensure assurance, protection, and welfare for citizens in fulfilling their fundamental health requirements. The social insurance framework employed in the program's execution comprises four principles: the principle of cooperation, the principle of mandatory participation, the principle of income-based contribution determination, and the principle of non-profit orientation. After a decade of the program, numerous issues persist, including incomplete participation, prohibitively high contributions resulting in arrears, and suboptimal program benefits. This study establishes the optimal structure of social insurance systems inside national health insurance. The employed study method is normative, analyzing applicable laws and regulations, supplemented by a legislative and comparative approach to identify the optimal framework for social insurance regulation. By analyzing legal materials using descriptive-analysis, the study's main findings reveal that although JKN has enrolled over 91% of Indonesia’s population, it still faces significant challenges, including delayed premium payments by participants and difficulties in achieving Universal Health Coverage (UHC). Compared to Thailand and Taiwan, JKN has yet to meet the UHC standards recognized by the WHO. The analysis concludes that the four foundational principles of social insurance within the national health insurance framework are insufficient; therefore, an additional four principles are required to ensure certainty, protection, and benefits for program participants, which is essential for the realization of the National Social Security System Law's objectives. The optimal design of a social insurance framework should include the principles of mutual cooperation, mandatory participation, proportional contributions, and non-profit operations. Abstrak Program jaminan kesehatan nasional di Indonesia bertujuan untuk memastikan jaminan, perlindungan, dan kesejahteraan bagi warga negara dalam memenuhi kebutuhan dasar kesehatan mereka. Kerangka kerja asuransi sosial yang digunakan dalam pelaksanaan program ini terdiri dari empat prinsip: prinsip kerja sama, prinsip kepesertaan wajib, prinsip penentuan iuran berdasarkan pendapatan, dan prinsip orientasi nirlaba. Setelah satu dekade program ini berjalan, masih terdapat beberapa permasalahan yang dihadapi, termasuk kepesertaan yang tidak lengkap, iuran yang terlalu tinggi sehingga menimbulkan tunggakan, dan manfaat program yang tidak optimal. Penelitian ini bertujuan untuk menentukan struktur sistem asuransi sosial yang optimal di dalam jaminan kesehatan nasional. Metode penelitian yang digunakan adalah normatif, menganalisis peraturan perundang-undangan yang berlaku, dilengkapi dengan pendekatan legislatif dan komparatif untuk mengidentifikasi kerangka kerja yang optimal untuk regulasi asuransi sosial. Dengan menganalisis bahan hukum menggunakan deskriptif-analisis, temuan utama studi ini mengungkapkan bahwa meskipun JKN telah mencakup lebih dari 91% penduduk Indonesia, JKN masih menghadapi tantangan yang signifikan, termasuk keterlambatan pembayaran premi oleh peserta dan kesulitan dalam mencapai Cakupan Kesehatan Semesta (Universal Health Coverage/UHC). Dibandingkan dengan Thailand dan Taiwan, JKN belum memenuhi standar UHC yang diakui oleh WHO. Analisis ini menyimpulkan bahwa empat prinsip dasar asuransi sosial dalam kerangka jaminan kesehatan nasional tidak cukup; oleh karena itu, diperlukan empat prinsip tambahan untuk memastikan kepastian, perlindungan, dan manfaat bagi peserta program, yang sangat penting untuk merealisasikan tujuan UU SJSN. Desain optimal dari kerangka kerja asuransi sosial harus mencakup prinsip-prinsip gotong royong, partisipasi wajib, iuran proporsional, dan operasi nirlaba.